The impact of child psychiatric conditions on future educational outcomes among a community cohort in Brazil. (28th October 2021) - Hoffmann, Mauricio Scopel; McDaid, David; Salum, Giovanni Abrahão; Silva-Ribeiro, Wagner; Ziebold, Carolina; King, Derek; Gadelha, Ary; Miguel, Eurípedes Constantino; Mari, Jair de Jesus; Rohde, Luis Augusto; Pan, Pedro Mario; Bressan, Rodrigo Affonseca; et al.
Abstract: Aims: Mental health problems early in life can negatively impact educational attainment, which in turn have negative long-term effects on health, social and economic opportunities. Our aims were to: (i) estimate the impacts of different types of psychiatric conditions on educational outcomes and (ii) to estimate the proportion of adverse educational outcomes which can be attributed to psychiatric conditions. Methods: Participants ( N = 2511) were from a school-based community cohort of Brazilian children and adolescents aged 6–14 years enriched for high family risk of psychiatric conditions. We examined the impact of fear- (panic, separation and social anxiety disorder, specific phobia, agoraphobia and anxiety conditions not otherwise specified), distress- (generalised anxiety disorder, major depressive disorder and depressive disorder not otherwise specified, bipolar, obsessive-compulsive, tic, eating and post-traumatic stress disorder) and externalising-related conditions (attention deficit and hyperactivity disorder, conduct and oppositional-defiant conditions) on grade repetition, dropout, age-grade distortion, literacy performance and bullying perpetration, 3 years later. Psychiatric conditions were ascertained by psychiatrists, using the Development and Well-Being Behaviour Assessment. Propensity score and inverse probability weighting were used to adjust for potential confounders, including comorbidity, and sample attrition. We calculated the population attributable risk percentages to estimate the proportion of adverse educational outcomes in the population which could be attributed to psychiatric conditions. Analyses were conducted separately for males and females. Results: Fear and distress conditions in males were associated with school dropout (odds ratio (OR) = 2.76; 95% confidence interval (CI) = 1.06, 7.22; p < 0.05) and grade repetition (OR = 2.76; 95% CI = 1.32, 5.78; p < 0.01), respectively. Externalising conditions were associated with grade repetition in males (OR = 1.66; 95% CI = 1.05, 2.64; p < 0.05) and females (OR = 2.03; 95% CI = 1.15, 3.58; p < 0.05), as well as age-grade distortion in males (OR = 1.66; 95% CI = 1.05, 2.62; p < 0.05) and females (OR = 2.88; 95% CI = 1.61, 5.14; p < 0.001). Externalising conditions were also associated with lower literacy levels ( β = −0.23; 95% CI = −0.34, −0.12; p < 0.001) and bullying perpetration (OR = 3.12; 95% CI = 1.50, 6.51; p < 0.001) in females. If all externalising conditions were prevented or treated, we estimate that 5.0 and 4.8% of grade repetition would not have occurred in females and males, respectively, as well as 10.2 (females) and 5.3% (males) of age-grade distortion cases and 11.4% of female bullying perpetration. Conclusions: The study provides evidence of the negative impact of psychiatric conditions on educational outcomes in a large Brazilian cohort. Externalising conditions had the broadest and most robust negative impacts on education and these were particularly harmful to females which are likely to limit future socio-economic opportunities.